Análise do sistema agroindustrial da carne ovina no Oeste do Paraná com o uso da matriz estrutural prospectiva - Ramos, Manoel João (2013)
This study presents an analysis of how institutional, organizational, technological and competitive environments, as well as strategies and performance of companies may influence the agribusiness system of lamb meat on western Paraná. To do that, the Prospective Structural Analysis was applied; it is a method under the matrix form of analysis of relations between the variables that constitute the studied system and those that belong to its explanatory context. This method aims to emerge the main essential variables to the evolution of the system. The theoretical concepts of New Institutional Economics were applied in combination with the Model of Systemic Relations, important analysis tools from the point of view of the importance of institutions and their influence in the transaction costs and alternative ways of organizing production. The practical application of the study occurs in three successive stages comprising the survey of variables that possibly affect the system, the identification of relationships between these variables and finally the selection of the relevant variables. The results derived from the analysis suggest that lamb meat industry rests under an environment of instability, having the illegal slaughter as variable of greatest influence and at the same time highly dependent which presents itself as an unstable variable and any action on it may cause significant impacts on the entire system. Although rated in the group of moderate influence, variables legislation and taxation / evasion were positioned in the quadrant of the input variables, indicating that they are, at the same time, very influential and little dependent, and should be targeted for priority actions. In this sense, the institutional environment should begin the process of improving the system of lamb meat because of the lack of specific legislations, the incidence of high taxes followed by tax evasion, has great influence on the lamb agro industrial system, undermining the competitiveness of the sector. Finally, it is observed that there are great challenges and opportunities for articulation of lamb meat agro industrial system in the Western Parana in order to promote better coordination between the agents involved in the system and the final consumer.